2017
DOI: 10.1186/s12913-017-2139-x
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to improve safety and efficiency of the ICU discharge process: a mixed methods study

Abstract: BackgroundEvidence indicates that suboptimal clinical handover from the intensive care unit (ICU) to general wards leads to unnecessary ICU readmissions and increased mortality. We aimed to gain insight into barriers and facilitators to implement and use ICU discharge practices.MethodsA mixed methods approach was conducted, using 1) 23 individual and four focus group interviews, with post-ICU patients, ICU managers, and nurses and physicians working in the ICU or general ward of ten Dutch hospitals, and 2) a q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 33 publications
2
34
0
3
Order By: Relevance
“…This nationally representative study identified 75 barriers to the success of the implementation of the perioperative safety guidelines, relating to time constraints, time pressure in emergency procedures, insufficient IT support and facilities, experienced increased workload, non-constructive attitudes and opinions toward the guidelines, lack of clinical documentation (i.e., missing, incomplete, or wrong information), suboptimal culture, lack of awareness, and knowledge about the importance and purpose, poor teamwork, lack of scientific evidence, complexity of the guidelines, lack of exposure to implementation efforts, suboptimal organizational preconditions, and lack of motivation to change behavioral routines. Several barriers already identified [ 19 , 27 , 29 32 ] were confirmed; these included a lack of time, inappropriateness in certain contexts such as emergencies, insufficient awareness, resisting opinions and insufficient knowledge of the professionals, inadequate IT infrastructures, social factors such as a suboptimal culture and collaboration (i.e., teamwork issues), skepticism regarding the evidence base, and inability to overcome the inertia of previous practice. However, we were not able to find other publications relating specifically to barriers concerning perioperative guidelines.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…This nationally representative study identified 75 barriers to the success of the implementation of the perioperative safety guidelines, relating to time constraints, time pressure in emergency procedures, insufficient IT support and facilities, experienced increased workload, non-constructive attitudes and opinions toward the guidelines, lack of clinical documentation (i.e., missing, incomplete, or wrong information), suboptimal culture, lack of awareness, and knowledge about the importance and purpose, poor teamwork, lack of scientific evidence, complexity of the guidelines, lack of exposure to implementation efforts, suboptimal organizational preconditions, and lack of motivation to change behavioral routines. Several barriers already identified [ 19 , 27 , 29 32 ] were confirmed; these included a lack of time, inappropriateness in certain contexts such as emergencies, insufficient awareness, resisting opinions and insufficient knowledge of the professionals, inadequate IT infrastructures, social factors such as a suboptimal culture and collaboration (i.e., teamwork issues), skepticism regarding the evidence base, and inability to overcome the inertia of previous practice. However, we were not able to find other publications relating specifically to barriers concerning perioperative guidelines.…”
Section: Discussionmentioning
confidence: 93%
“…By including different perioperative key disciplines from different types and sizes of hospitals, covering a representative sample of nine hospitals with geographic spread to cover multiple regions across the Netherlands, we ensured a breadth of perspectives, increasing the generalizability of our research. This generalizability may even partly hold for other areas than the perioperative one; some of the barriers and facilitators probably do not only apply for guideline implementation in the perioperative setting, since similar barriers and drivers have been previously identified as determinants influencing the implementation of change in healthcare [ 19 , 27 30 , 31 ]. The themes that emerged from this research probably represent the determinants that play a role in the implementation of many change initiatives in healthcare and hence present a valuable learning opportunity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To improve ICU nurses’ perceptions, strategies such as individualized care planning to better facilitate patients’ transition from the ICU (Haggstrom, Asplund, & Kristiansen, ) or ensuring more effective teamwork and regularly using assessment tools that improve communication of patient information may be necessary (Lin, Chaboyer, & Wallis, ). Other strategies, such as formulating specific discharge criteria, stimulating a culture of feedback, preventing overestimation of the possibilities of caring for complex patients on the general ward by ICU physicians, and encouraging greater handover communication, should be implemented as well (van Sluisveld et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…24 The study shows the cultural difference between the ICU and the general ward as a barrier in this transitional care, as well as the physical separation of the ICU from the other sectors of the hospital, leading to lack of knowledge and misunderstanding in the communication process. 25 Influence as facilitators for these moments of transition: good professional-patient communication and among professionals; early education for the discharge of patients; the use of tools that facilitate this process such as the use of guidelines and policies; the education and training of professionals involved in transitional care and the transition process. 23 It reinforces the importance of the role of the nurse as a care manager, a professional who must establish a bond with the patient, capturing their needs and becoming a partner in the formulation and implementation of care.…”
Section: (A17 A19 A4 A13 and A5)mentioning
confidence: 99%